Technological Traditions in the Decoration of Early Neolithic Pottery on the Kola North - Alevtina M. Kiseleva (Археология евразийских степей, 2023)
The article presents the results of the study of the ornamentation technique on the Early Neolithic vessels (ca. 5300–4500 calBC) in the North of the Kola. Four ornamental techniques have been identified on the ceramics studied: stamping, puncturing, puncturing-incising and stepping. Also different variants of application of pits are revealed (with «pearls» on the inner side or without them). In order to identify the traditions of decoration the co-occurrence of different techniques on 105 good preserved vessels was considered. The ornamental features of the vessels were compared with morphological aspects (bottom and rim shapes). As a result, stable combinations of techniques were identified, and it was also found that the vessels of different shapes are characterized by various techniques of ornamentation. Flat-bottomed vessels are decorated only by stamping, while round-bottomed ones show all the techniques observed.